MONOPOLI DI BIDANG TEKNOLOGI INFORMASI - Enzus Tinianus (Jurnal Hukum Samudra Keadilan, 2021)
Competition in the business world causes business actors to sometimes resort to various ways to conduct unfair business competition, resulting in losses for other business actors. In the virtual world (information technology for example) this action is often found. So it is necessary to study how the prohibition of monopolistic practices and unfair business competition against businesses in the field of information technology. This research is a normative legal research, the main data of which is obtained through library research. Based on the results of the research, it is known that the form of market monopoly and unfair business competition in information technology law can be in the form of vertical integration, discrimination of business actors, taking of domain names, and other actions that can harm business competitors. The Tying Arrangement in the Microsoft case is a form of unfair business competition, in which the giant software company Microsoft is accused of violating the antitrust law by taking Tying Arrangements by linking the windows product (the tying product) with the internet explorer browser product (the tied product). The Tying Arrangement was allegedly carried out in order to win a monopoly in the internet browser product market.